Peran Perceived Value Dalam Memediasi Pengaruh E-Wom Terhadap Minat Beli Mahasiswa Generasi Z di Universitas Perjuangan Tasikmalaya (Shopee Case Study) - Ashari, Riki Aksan Aji; Huhamad Pauzy, Depy; Nafilah Faza, Shita; Nugraha, Helmi; Husni Herlisana Putra, Fajril (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This research aims to analyze the role of perceived value in mediating the effect of electronic word of mouth (e-WOM) on the purchase intention of Generation Z students who use Shopee at Universitas Perjuangan Tasikmalaya. This study employed a quantitative, survey-based approach. The sampling technique used was purposive sampling with a total of 100 respondents who had previously made purchases through Shopee. Data were collected using an online questionnaire measured with a five-point Likert scale. . The results indicate that e-WOM has a positive and significant effect on both perceived value and purchase intention. Furthermore, perceived value has a positive and significant effect on purchase intention and partially mediates the relationship between e-WOM and purchase intention. These findings suggest that user-generated content, such as reviews and recommendations on the Shopee platform, enhances consumers’ perceived value, thereby increasing their purchase intention.